Techno-economics of industrial scale beta-ß-D-fructofuranosidase and short-chain fructooligosaccharides production - Shedlock, Matthew (Stellenbosch : Stellenbosch University, 2014)
Thesis (MEng)--Stellenbosch University, 2014.